O hipertexto na escola: a retextualização digital nas aulas de língua portuguesa - Primo, Eloíza Martins [UNESP] (2015)
With the advent of the Internet and new technologies, changes in reading and writing have generated discussions regarding the best way to proceed in the process of teaching and learning of readers and writers skills in school. This qualitative research has as object of study observe the digital genres and hypertext in the classroom and how they provide the student a greater interaction with these new forms of literacy. We understand that provide multiple semiosis (texts, images and sounds) on the nature of the used language resources and seek to understand how they can improve and enhance the development of reader and writer skills. The research undertaken here aims to study strategies that can be adapted to hypertext teaching, from the printed text of the concepts that most students have mastered through a Didactic Sequence. By doing this, students in 9th grade of elementary school in a public school will produce a retextualization in Wiki platform